KINERJA DINAS PERHUBUNGAN KOTA DENPASAR DALAM PELAKSANAAN AREA TRAFFIC CONTROL SYSTEM - I Dewa Putu Hery Priyana; I Made Adiwidya Yowana; Ronald Umbas (Sekolah Tinggi Ilmu Sosial Politik Wira Bhakti, 2022)
This study aims to reveal whether the implementation of the ATCS system has an effect on the performance of the Denpasar City Transportation Service. This study was conducted at the Office of Technical Implementation Unit of Land Transportation Services. The researchers used qualitative descriptive approach. To collect the data, researchers conducted interviews and direct observations. The questions given to the respondents were made based on five predetermined indicators. The analysis on the collected data shows that the implementation of ATCS system in Denpasar City is able to improve the work performance of the Office.